Supersimetria, método variacional e potencial de Lennard-Jones (12,6) - de Araujo, João Cesar Boreggio [UNESP]; Borges, Gláucia R.P. [UNESP]; Drigo Filho, Elso [UNESP] (FapUNIFESP (SciELO), 2006)
In this work a review of the supersymmetric quantum mechanics formalism combined with the variational method is done. This approach is useful in order to obtain numerical values for the energy eigenvalues from Schrödinger equation. As an example, the energy eigenvalues from the Lennard-Jones (12,6) potential are determined and the results are compared with other ones obtained from different methods. Copyright by the Sociedade Brasileira de Física.
Supersymmetry, variational method and Lennard-Jones (12,6) potential
Keywords: Lennard-Jones potential; Quantum mechanics; Supersymmetry; Variational method